Improving knowledge and attitude to tackle COVID-19 transmission in a health care facility of North Sumatra’s village - Evita Mayasari; Lokot D. Lubis; Nuraiza Meutia; Cut A. Adella; Eka R. Megawati (Journal of Community Service and Empowerment, 2023)
COVID-19 hits Indonesia with massive social restrictions in many aspects of life. In some Indonesian rural areas, information related to the pandemic through online platforms and social media is accessible. However, most of the information is inaccurate. Improving individual knowledge is crucial to support the government’s campaign for COVID-19 prevention. This cross-sectional, pretest-posttest study aims to evaluate the knowledge and attitude of health personnel toward COVID-19 prevention in a primary healthcare facility in a rural area of North Sumatra. All twenty-two health personnel who worked in the hospital during the study were asked to fill in a two-sectioned questionnaire. The first section contained questions related to knowledge, and the second section was related to attitude toward COVID-19. Following the educational activity, each health personnel filled in the same questionnaire again. We analyzed the data statistically using two-way ANOVA (p<0.05, 95% CI). There were increases in knowledge (p < 0.001) and attitude (p = 0.0002) of the health personnel after the educational activity. Educational activity improves health personnel’s knowledge and attitude regarding COVID-19 prevention.